Development of a Framework for the Systematization of Metro Line Projects - Gabarra, Murilo Macedo; Silva, Helena Aparecida Ayoub (National Journal of City Management, 2025)
Objective – This study aims to systematize the design processes of metro lines using Geographic Information Systems (GIS), through the development of a digital cartographic database based on public data sources, in order to support decision-making in the planning of metro lines in the city of São Paulo. Methodology – The methodology is based on the application of geoprocessing techniques to map environmental, urban, and legal constraints, such as the presence of contaminated areas, heritage-listed buildings, and building density parameters. Open data from public agencies, such as the Environmental Company of the State of São Paulo (CETESB) and the Geosampa platform, were used to structure the database and generate thematic maps. Originality/Relevance – The originality of this work lies in the systematization of site and route selection processes for metro lines through a GIS-based approach, contributing to a key phase in the design of underground transportation infrastructure. Results – As a result of the proposed method, thematic maps were produced, organized into categories related to station location and metro line routing. These outputs serve as support tools for the planning and preliminary design of metro line projects. Theoretical/methodological contributions – By integrating multiple geospatial data sources and constraint mapping techniques, this study offers a replicable tool for urban infrastructure planning, contributing to innovation in the design of underground public transportation systems in large urban centers. Social and environmental contributions – The methodology contributes to planning transparency, reduction of socio-environmental impacts, and the expansion of equitable access to urban mobility.